1978
DOI: 10.1159/000114930
|View full text |Cite
|
Sign up to set email alerts
|

Bromocryptine in Levodopa Response-Losing Parkinsonism

Abstract: 23 patients with advanced Parkinson’s disease were allocated in a double-blind study of bromocryptine. These patients had an insufficient or deteriorating response to levodopa treatment. The dosages of levodopa were optimal and stabilized 3 months prior to and during this 5-month study. The addition of bromocryptine in high doses (average daily dose 71 mg) induced a significant improvement in the total score of the Webster and the NUDS scales. The global assessment, both by the investigator and by the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Six of eight coordinators responded. 13,14,16,17,19,20 One trialist was deceased and therefore the requested information could not be retrieved. 18…”
Section: Methodologic Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Six of eight coordinators responded. 13,14,16,17,19,20 One trialist was deceased and therefore the requested information could not be retrieved. 18…”
Section: Methodologic Qualitymentioning
confidence: 99%
“…Only one trial reported age at onset. 13 The mean disease duration ranged from 8.5 18,19 to more than 13 years. 14 There were substantial differences between the studies with regard to the mean pretrial daily dosages of LD and the reported ratios of LD/decarboxylase inhibitor.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations